Ubiór czyni Rzymianina? Styl życia, folusznicy i romanizacja rzymskiej prowincji Panonii (I-III wiek n.e.). - Kaczmarek , Zofia (Studia Europaea Gnesnensia, 2020)
The paper discusses the role of attire in the process of Romanization of Pannonia. Special emphasis is placed on the probability of clothes having been fulled in the province. Since fulling was a matter of personal interest, not necessity, the emergence of the fullonicae could be considered as a symptom of embracing Roman way of life and thus Roman culture.